Dynamisch-mechanische Polymerpartikelverrundung zur Verbesserung der Fließfähigkeit für das selektive Lasersintern - Ponusamy, SathishKumar; Schmid, Hans-Joachim

Tax Education After WWII: How Spain, the USA, and West Germany Tried to Make Their Citizens Pay Honestly - Schönhärl, Korinna; Düll, Nasrin; Ramírez Lugo , Nadya Melina (Tax Evasion and Tax Havens since the Nineteenth Century)
State education in honest tax payment can be understood as a facet of training in citizenship, i.e. as an attempt by the modern state to standardize the behavior of its citizens and to prevent deviations. Based on this Foucauldian understanding, this exploratory article examines tax education in the United States, Spain, and West Germany from the mid-1940s to the late 1980s. During this period, the USA asserted itself as the champion of tax education and Spain consistently tried to emulate this example, albeit with more modest means and different semantic strategies from as early as the 1960s, when it was still under a autoritarian regime. The FRG, however, completely discontinued its few early attempts at tax education from the mid-1950s onwards. Even during the economic crises and tax scandals of the 1970s, there was no relaunch of the programs. The article locates the reasons for this highly uneven development in the different ideal images of the citizen in the three states.

Feasibility Study of Compression Molding for Large Reinforcement Structures in the Commercial Vehicle Sector - Lückenkötter, Julian; Leimbach, J.P.; Stallmeister, Tim; Marten, Thorsten; Tröster, Thomas (Materials Research Proceedings)
Abstract. Due to an increasing volume of shipments, there is a significant need for more delivery vehicles. One approach to reduce the associated increase in carbon dioxide (CO2) emissions is a new light weight design approach involving the substitution of conventional materials with glass fiber mat-reinforced thermoplastics (GMT) based on polypropylene (PP). The application of GMT by compression molding is a widely used process in the automotive industry. However, application in the commercial vehicle sector requires much larger dimensions, making it necessary to clarify whether the manufacturing process and material are suitable for semi-structural applications on this scale. To find this out, two replacement geometries are abstracted in this study and manufactured by varying the main manufacturing parameters. The feasibility can be demonstrated by recording and analyzing the resulting process variables and measuring the formed fiber distribution. At the end of the paper, recommendations are given for the production of GMT structures on the scale of commercial vehicles.
Keywords: Compression Molding; Fiber Content; Process Development; Lightweight Design

Selective Discrimination between CO and H2 with Copper–Ceria-Resistive Gas Sensors - Baier, Dominik; Priamushko, Tatiana; Weinberger, Christian; Kleitz, Freddy; Tiemann, Michael (ACS Sensors)
The production of hydrogen and the utilization of biomass for sustainable concepts of energy conversion and storage require gas sensors that discriminate between hydrogen (H2) and carbon monoxide (CO). Mesoporous copper–ceria (Cu–CeO2) materials with large specific surface areas and uniform porosity are prepared by nanocasting, and their textural properties are characterized by N2 physisorption, powder XRD, scanning electron microscopy, transmission electron microscopy, and energy-dispersive X-ray spectroscopy. The oxidation states of copper (Cu+, Cu2+) and cerium (Ce3+, Ce4+) are investigated by XPS. The materials are used as resistive gas sensors for H2 and CO. The sensors show a stronger response to CO than to H2 and low cross-sensitivity to humidity. Copper turns out to be a necessary component; copper-free ceria materials prepared by the same method show only poor sensing performance. By measuring both gases (CO and H2) simultaneously, it is shown that this behavior can be utilized for selective sensing of CO in the presence of H2.
Keywords: Fluid Flow and Transfer Processes; Process Chemistry and Technology; Instrumentation; Bioengineering

Proof of concept for incremental sheet metal forming by means of electromagnetic and electrohydraulic high-speed forming - Holzmüller, Maik; Linnemann, Maik; Homberg, Werner; Psyk, Verena; Kräusel, Verena; Kroos, Janika (Materials Research Proceedings)
Abstract. The combination of incremental sheet metal forming and high-speed forming offers new possibilities for flexible forming processes in the production of large sheet metal components of increased complexity with relatively low forming energies. In this paper, the general feasibility and process differences between the pulse-driven high-speed forming technologies of electrohydraulic and electromagnetic forming were investigated. An example component made of EN AW 6016 aluminum sheet metal was thus formed incrementally by both processes and the forming result evaluated by an optical 3D measurement system. For this purpose, a forming strategy for electromagnetic incremental forming (EMIF) was developed, tested and adapted to the electrohydraulic incremental forming process (EHIF). The discharge energy, the tool displacement and the pressure field of the forming zone were determined as relevant parameters for the definition of an adequate tool path strategy. It was found that the EHIF process is less affected by larger distances between the tool and the blank, while this is a critical variable for force application to the component during EMIF. On the other hand, the more uniform pressure distribution of the EMIF process is advantageous for forming large steady component areas.
Keywords: Incremental Sheet Forming; Aluminium; High-Speed Forming

Investigation of Pressure Fields Generated by Two Simultaneous Discharges in Liquid Initiated by Wires - Knyazyev, Mykhaylo; Holzmüller, Maik; Homberg, Werner (Journal of Manufacturing and Materials Processing)
The pressure fields generated by two simultaneous discharges have not been investigated on any notable scale for the electrohydraulic impulse forming method. In this study, the synchronicity of two discharges is ensured by the sequential connection of two wires mounted in two spark gaps in a common volume of liquid. The objective is to experimentally confirm the equilibrium of the energies evolved in two spark gaps by means of pressure measurements. In addition, multipoint membrane pressure gauges demonstrated the feasibility of easily recording detailed pressure maps. Based on the membrane deformation mechanism and material strengthening under static and impulse conditions, the processing procedure is further developed so as to achieve better accuracy in the determination of pressure field parameters. The practical equality of the pressure fields on the left and right halves of the flat-loaded area confirms the equality of energies evolved in the two spark gaps. The direct shock waves create zones with the most intensive loading. These results provide a basis for the development of new electrohydraulic technologies involving the application of two simultaneous discharges with equal energy and pressure parameters.
Keywords: impulse; forming; electrohydraulic; discharge; wire; pressure gauge; pressure field

Studien zu Schulleistungen und ihre Aufbereitung - Neumann, Phillip (Zeitschrift für Heilpädagogik)
Keywords: Inklusion; Sonderpädagogik; Bildung; Bildungsstudien; Integration

Wässrige Glucosaminlösung als neues Lösungsmittel zur CO2-Abscheidung - Hami Dindar, Iman; Lutters, Nicole; Kenig, Eugeny (Jahrestreffen der ProcessNet-Fachgruppen Fluidverfahrenstechnik und Adsoprtion)

Understanding the Redox Mechanism of Sulfurized Poly(acrylonitrile) as Highly Rate and Cycle Stable Cathode Material for Sodium-Sulfur Batteries - Kappler, Julian; Tonbul, Güldeniz; Schoch, Roland; Murugan, Saravanakumar; Nowakowski, Michał; Lange, Pia Lena; Klostermann, Sina Vanessa; Bauer, Matthias; Schleid, Thomas; Kästner, Johannes; Buchmeiser, Michael Rudolf (Journal of The Electrochemical Society)
Room temperature sodium-sulfur (RT Na-S) batteries are considered potential candidates for stationary power storage applications due to their low cost, broad active material availability and low toxicity. Challenges, such as high volume expansion of the S-cathode upon discharge, low electronic conductivity of S as active material and herewith limited rate capability as well as the shuttling of polysulfides (PSs) as intermediates often impede the cycle stability and practical application of Na-S batteries. Sulfurized poly(acrylonitrile) (SPAN) inherently inhibits the shuttling of PSs and shows compatibility with carbonate-based electrolytes, however, its exact redox mechanism remained unclear to date. Herein, we implement a commercially available and simple electrolyte into the Na-SPAN cell chemistry and demonstrate its high rate and cycle stability. Through the application of in situ techniques utilizing electronic impedance spectroscopy (EIS) and X-ray absorption spectroscopy (XAS) at different depths of charge and discharge, an insight into SPAN’s redox chemistry is obtained.
Keywords: Materials Chemistry; Electrochemistry; Surfaces; Coatings and Films; Condensed Matter Physics; Renewable Energy; Sustainability and the Environment; Electronic; Optical and Magnetic Materials

Methodology for Certification-Compliant Effect-Chain Modeling - Gräßler, Iris; Wiechel, Dominik; Koch, Anna-Sophie; Sturm, Tim; Markfelder, Thomas (Systems)
The success of engineering complex technical systems is determined by meeting customer requirements and institutional regulations. One example relevant to the automobile industry is the United Nations Economic Commission of Europe (UN ECE), which specifies the homologation of automobile series and requires proof of traceability. The required traceability can be achieved by modeling system artifacts and their relations in a consistent, seamless model—an effect-chain model. Currently, no in-depth methodology exists to support engineers in developing certification-compliant effect-chain models. For this purpose, a new methodology for certification-compliant effect-chain modeling was developed, which includes extensions of an existing method, suitable models, and tools to support engineers in the modeling process. For evaluation purposes, applicability is proven based on the experience of more than 300 workshops at an automotive OEM and an automotive supplier. The following case example is chosen to demonstrate applicability: the development of a window lifter that has to meet the demands of UN ECE Regulations R156 and R21. Results indicate multiple benefits in supporting engineers with the certification-compliant modeling of effect chains. Three benefits are goal-oriented modeling to reduce the necessary modeling capacity, increasing model quality by applying information quality criteria, and the potential to reduce costs through automatable effect-chain analyses for technical changes. Further, companies in the automotive and other industries will benefit from increased modeling capabilities that can be used for architecture modeling and to comply with other regulations such as ASPICE or ISO 26262.
Keywords: Information Systems and Management; Computer Networks and Communications; Modeling and Simulation; Control and Systems Engineering; Software

Characterization of Na-S Battery System Using X-ray Absorption Spectroscopy - Tonbul, Güldeniz; Kappler, Julian; Murugan, Saravanakumar; Schoch, Roland; Nowakowski, Michal; Lange, Pia; Bauer, Matthias; Buchmeiser, Michael R.

Simulation Environment for Traffic Control Systems Targeting Mixed Autonomy Traffic Scenarios - Link, Christopher; Malena, Kevin; Gausemeier, Sandra; Trächtler, Ansgar (Proceedings of the 9th International Conference on Vehicle Technology and Intelligent Transport Systems)
The development of autonomous vehicles and their introduction in urban traffic offer many opportunities for traffic improvements. In this paper, an approach for a future traffic control system for mixed autonomy traffic environments is presented. Furthermore, a simulation framework based on the city of Paderborn is introduced to enable the development and examination of such a system. This encompasses multiple elements including the road network itself, traffic lights, sensors as well as methods to analyse the topology of the network. Furthermore, a procedure for traffic demand generation and routing is presented based on statistical data of the city and traffic data obtained by measurements. The resulting model can receive and apply the generated control inputs and in turn generates simulated sensor data for the control system based on the current system state.
Keywords: Traffic Simulation; Traffic Control; Car2X; Mixed Autonomy; Autonomous Vehicles; SUMO; Sensor Simulation; Traffic Demand Generation; Routing; Traffic Lights; Graph Analysis; Traffic Observer

Business Models for Cultural Event Platforms – A Taxonomy Approach - Althaus, Maike; Müller, Michelle; Vorbohle, Christian; Kundisch, Dennis (Proceedings of the International Conference on Challenges in Managing Smart Products and Services (CHIMSPAS 2023))

May I have your Attention, please? – The Interaction between Attention Screening and Reputation on Crowdworking Platforms - Laux, Florian; Poniatowski, Martin; Kundisch, Dennis (Proceedings of the 31st European Conference on Information Systems (ECIS))

Particles as Seeds for Instabilities in Uniaxially Elongated Polymer Suspension Filaments (Presentation) - Neukötter, Moritz; Jesinghausen, Steffen; Schmid, Hans-Joachim

Haushaltswissenschaft – Eine Diskussionsgrundlage - Küster, Christine; Klünder, Nina; Wagenknecht, Inga (Hauswirtschaft und Wissenschaft)

The Complexity of Translationally Invariant Problems beyond Ground State Energies - Gharibian, Sevag; Watson, James; Bausch, Johannes (Proceedings of the 40th International Symposium on Theoretical Aspects of Computer Science (STACS))

Large-Scale Formation of DNA Origami Lattices on Silicon - Tapio, Kosti; Kielar, Charlotte; Parikka, Johannes M.; Keller, Adrian; Järvinen, Heini; Fahmy, Karim; Toppari, J. Jussi (Chemistry of Materials)
Keywords: Materials Chemistry; General Chemical Engineering; General Chemistry

Nanoparticle‐Based Formulations of Glycopeptide Antibiotics: A Means for Overcoming Vancomycin Resistance in Bacterial Pathogens? - Pothineni, Bhanu Kiran; Keller, Adrian (Advanced NanoBiomed Research)
Keywords: General Medicine

Effect of Ionic Strength on the Thermal Stability of DNA Origami Nanostructures - Hanke, Marcel; Tomm, Emilia; Grundmeier, Guido; Keller, Adrian (ChemBioChem)
Keywords: Organic Chemistry; Molecular Biology; Molecular Medicine; Biochemistry